ANALISIS KONTROL DIRI SISWA PADA KELAS X SMK NEGERI 03 PONTIANAK - Mila Pratiwi; Luhur Wicaksono; Indri Astuti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractSelf-control is very important to have so that individuals do not always behave negatively, this attitude can be embedded in students from an early age so that unwanted things do not occur within the school environment or outside the school environment. The general problem in this research is: "How is the analysis of student self control in Class X SMK Negeri 03 Pontianak?". From these general problems, it is intended that researchers can obtain more in-depth results from the analysis of student self-control in class X SMK Negeri 03 Pontianak. In this research, the method used is descriptive method. The form of the research is a survey study. The population in this study were 128 students and the sample was 34 students in class X SMK Negeri 03 Pontianak. This study uses a quantitative approach. Data collection techniques used are indirect communication techniques and data collection tools with questionnaires. While the data analysis technique used the percentage formula. Based on the results of this analysis research, students' self-control as referred to in how to control behavior, modify stimuli, anticipate events and choose actions, each aspect has gone "well".Keywords: Analysis Quantitative, Self Control